1994
DOI: 10.2307/3431782
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Chromium

Abstract: The production of reactive oxygen species on addition of hexavalent chromium (potassium dichromate, K2Cr2O7) to lung cells in culture was studied using flow cytometer analysis. A Coulter Epics Profile II flow cytometer was used to detect the formation of reactive oxygen species after K2Cr2O7 was added to A549 cells grown to confluence. The cells were loaded with the dye, 2',7'-dichlorofluorescein diacetate, after which cellular esterases removed the acetate groups and the dye was trapped intracellularly. React… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…This raises the question, What is known about the mechanism of action of potassium dichromate? Chromate crosses biological membranes and has a strong oxidative power that produces a high concentration of reactive species of O 2 inside cells (Bassi et al, 1990; Taylor et al, 1979; Witmer et al, 1994), which can impair the photopigments. Baszynski (1981) reported that chromate strongly decreases the pigment content, inhibits photosystem II activity, and disorganizes the fine structure of chloroplasts of Lemna minor Whether the observed effect of higher maximum chromium toxicity at high light conditions is the result of a specific interaction, for example, caused by an increase of the redox potential of potassium dichromate enhancing its oxidative power, is not clear and can only be speculated.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question, What is known about the mechanism of action of potassium dichromate? Chromate crosses biological membranes and has a strong oxidative power that produces a high concentration of reactive species of O 2 inside cells (Bassi et al, 1990; Taylor et al, 1979; Witmer et al, 1994), which can impair the photopigments. Baszynski (1981) reported that chromate strongly decreases the pigment content, inhibits photosystem II activity, and disorganizes the fine structure of chloroplasts of Lemna minor Whether the observed effect of higher maximum chromium toxicity at high light conditions is the result of a specific interaction, for example, caused by an increase of the redox potential of potassium dichromate enhancing its oxidative power, is not clear and can only be speculated.…”
Section: Discussionmentioning
confidence: 99%
“…Cr(VI) salts such as potassium dichromate (K 2 Cr 2 O 7 ) or chromic acid are widely used in leather, chrome-plating, and dye-producing industries [20, 21]. Occupational and environmental exposure to Cr(VI)-containing compounds is known to be toxic, mutagenic, and carcinogenic to human beings and diverse animals [2224], leading to serious damage to the kidneys [25, 26], liver [27, 28], lungs [29, 30], skin [31], and other vital organs [3234]. …”
Section: Introductionmentioning
confidence: 99%
“…The high TG level along with decreased absorption of fatty acids by adipose tissue is associated with a low level of HDL-C, insulin resistance and increased risk of atherosclerosis [27]. In our study, high cholesterol level in chromium intoxication may also be due to decreased activity of cytochrome P450 enzymes [28]. The rise in serum lipid profile may also be attributed to increased lipolysis, mediated by increased norepinephrine release which act through interference with the intracellular functions of Ca +2 in the cytoplasm [29].…”
Section: Discussionmentioning
confidence: 72%